Management of generic drug development: challenges and opportunities - Patil, Sandeep (Henry Stewart Talks, 2022)
Generic drugs, Project management, Indian perspective, Generics production and sales, Patent cliff, Quality by design, Product pricing, Drug launch time, Lifecycle management, Market penetration, Cost management, Scope creep, Project management, Cross-cultural communication